The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1021/acs.jnatprod.6b00310
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of Salpichrolides A, C, and G by Three Filamentous Fungi

Abstract: Incubation of salpichrolide A (1) with Rhizomucor miehei produced hydroxylation in rings B and C (C-7 and C-12) and led to C-5-C-6 epoxide opening, while incubation of salpichrolides C (2) and G (3) with R. miehei led to epoxide opening at the C-24-C-25 and C-5-C-6 positions, respectively. Biotransformation of salpichrolide A (1) with Cunninghamella elegans produced stereoselective hydroxylated, oxidized, and reduced derivatives in different positions of the A, B, and C rings and C-5-C-6 epoxide opening. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Biotransformation is superior to chemical synthesis due to superior regio-and stereo-selectivities, 1 environmentally friendly procedures, 2 and mild reaction conditions. 3 Biocatalysts play an important role in regio-and stereo-selective reactions, 4,5 including acetylation, 6 hydroxylation, 7 and epoxidation of steroids. 8 Our previous studies have shown that many transformations have been achieved by microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Biotransformation is superior to chemical synthesis due to superior regio-and stereo-selectivities, 1 environmentally friendly procedures, 2 and mild reaction conditions. 3 Biocatalysts play an important role in regio-and stereo-selective reactions, 4,5 including acetylation, 6 hydroxylation, 7 and epoxidation of steroids. 8 Our previous studies have shown that many transformations have been achieved by microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…The salpichrolide derivatives tested ( 2 – 11 ) were obtained by biotransformation of salpichrolides A, C, and G with filamentous fungi Rhizomucor miehei (CECT 2749) and Cunninghamella elegans (CECT 2113) ( Fig. ) . The results, expressed as half maximal inhibitory concentration ( IC 50 ), are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Salpichrolide derivatives obtained by biotransformation assayed against human prostate and breast cancer cell lines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biotransformation mediated by filamentous fungi consists of a powerful method to perform chemical modifications of a variety of starting materials such as bioactive natural products, to obtain derivatives with improved biological properties or even new biological activities [ 8 ]. This approach stands out as a promising alternative to conventional chemical methods since fungi contain multi-enzymatic systems with broad specificities and are, therefore, able to catalyse chemo, regio and stereoselective reactions on non-activated molecular sites that are normally unreactive or difficult to reach chemically [ 9 ]. Furthermore, microbial transformation is a fast, efficient, cost-effective and ecologically friendly technique because it requires only mild reaction conditions [ 10 ].…”
Section: Introductionmentioning
confidence: 99%